Root canal dressings for revascularization influence in vitro mineralization of apical papilla cells - Juliana Garuba RAHHAL; Emanuel da Silva ROVAI; Marinella HOLZHAUSEN; Celso Luiz CALDEIRA; Carlos Ferreira dos SANTOS; Carla Renata SIPERT (University of São Paulo, 2019)
Abstract Endodontic revascularization is based on cell recruitment into the necrotic root canal of immature teeth after chemical disinfection. The clinical outcome depends on the ability of surviving cells from the apical tissue to differentiate and promote hard tissue deposition inside the dentinal walls. Objective To investigate the effect of calcium hydroxide (CH) and modified triple antibiotic paste (mTAP - ciprofloxacin, metronidazole and cefaclor) on the viability and mineralization potential of apical papilla cells (APC) in vitro . Material and Methods APC cultures were kept in contact with CH or mTAP (250-1000 µg/mL) for 5 days, after which cell viability was assessed using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Next, APCs were subjected to CH or mTAP at 250 µg/mL for 5 days before inducing the differentiation assay. After 14 and 21 days, calcium deposition was assessed by the Alizarin Red S staining method, followed by elution and quantification using spectrophotometry. Data were analyzed using ANOVA followed by Tukey post hoc test. Results CH induced cell proliferation, whereas mTAP showed significant cytotoxicity at all concentrations tested. APC treated with CH demonstrated improved mineralization capacity at 14 days, while, for mTAP, significant reduction on the mineralization rate was observed for both experimental periods (14 and 21 days). Conclusion Our findings showed that CH induces cell proliferation and improves early mineralization, whereas mTAP was found cytotoxic and reduced the mineralization potential in vitro of APCs.